"We Say, When We've Reached One We've Reached the World...but What if We Missed One?" (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
Discussion of the conflict and peace process in Northern Ireland.
Keywords: Peace Process; Northern Ireland